The significance of sour cherry in iron supplementation - Nemes, Andrea; Baranyai, Edina; Remenyik, Judit (Acta Agraria Debreceniensis, 2015)
The iron concentration of ’Csengődi csokros’, ’Debreceni- and ’Érdi bőtermő’ , ‘Éva’, ’Kántorjánosi’ ,’Petri’ and the ’Újfehértói fürtös’ cultivars was determined by ICP-MS. Furthermore the Vitamin C, L-Malis acid and Citric acid concentration of samples were measured.Our results show that large amount Fe2+ (average 20.5 mg kg-1) accumulates in the pulp of sour cherry. Besides, the concentration of Vitamin C, L-Malis acid, that increase the absorption of iron, are high. Based on these results, the sour cherry and the products of sour cherry play an important role in the forming of iron content in body.